Cultural Industries from an Economic/Business Research Perspective - McFadyen, Stuart (Canadian Journal of Communication, 2000)
This article reviews, and provides a context for, the cultural industries research carried out by the authors over the last 20 years. This work focuses on the television and feature film industries and uses a micro-economic analysis approach which recognizes the three unusual economic characteristics of feature films and television programs: they suffer a cultural discount when traded across international borders, they are joint consumption goods, and they may result in external benefits. The work encompasses industry studies of Canadian broadcasting, U.S. domination of international trade in audiovisual products, international co-production, and new media.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMDB2MjVuMWExMTQ2